From use to impact: different approaches to Spanish e-Government - Fernando Fernandez-Bonilla (International Telecommunications Society (ITS), 2024)
This paper studies the determinants of egovernment use in Spain, a country highly ranked in the UN E-Government Development Index. Utilizing a logit model and recent national data (2023), the study identifies key factors influencing egovernment usage, such as time and cost savings, and examines user characteristics in relation to the digital divide. Additionally, the paper aims to advance the definitions of the second and third levels of the digital divide to adapt them to current realities. The findings highlight the importance of ICT skills, trust in technology, and quality internet connectivity for effective e-government participation. Policy recommendations are provided to bridge the digital divide and improve e-government adoption among vulnerable groups, emphasizing the need for targeted support and education to enhance digital skills and trust in e-government services.
Keywords: 330; e-Government; Logit; Internet; Digital Divide; e-Trust